Computer simulation of positive streamer dynamics in strongly non-uniform electric fields in air. Effect of applied voltage on a streamer velocity for different needle radii - Manuilenko, O.V.; Golota, V.I. (Вопросы атомной науки и техники, 2014)
The results of numerical simulations of the propagation of a positive streamer in air are presented. The positive streamer dynamics in the strongly non-uniform electric fields in air was investigated for wide set of applied voltages and needle radii. It is shown that qualitatively the dynamics of positive streamer in air does not differ from the negative streamer dynamics in nitrogen. Namely, streamer velocity has the same behavior in time during propagation in discharge gap, and the same trends with applied voltage increase and with decrease of needle radius.